Genetic Risk Scores Predict Recurrence of Acute Coronary Syndrome. (April 2016) - Vaara, Satu; Tikkanen, Emmi; Parkkonen, Olavi; Lokki, Marja-Liisa; Ripatti, Samuli; Perola, Markus; Nieminen, Markku S.; Sinisalo, Juha
Abstract : Background—: Several clinical risk estimation tools have established their role in the prediction of recurrence of acute coronary syndrome (ACS), but the value of genetic risk scores (GRSs) remains unclear. We examined how well 2 different GRSs estimate recurrent ACS and whether clinical factors are associated with GRSs. Methods and Results—: A cohort of 2090 consecutive patients with ACS who underwent coronary angiography between July 2006 and March 2008 in a single tertiary center was genotyped and prospectively followed up for a median of 5.5 years. We formed 2 partially overlapping GRSs: GRS47 of 47 single-nucleotide polymorphisms with previously reported significant association with coronary artery disease and GRS153 of 153 single-nucleotide polymorphisms with significant or suggestive association with coronary artery disease. GRS47 showed association with recurrent ACS independent of clinical factors ( P =0.037; hazard ratio, 1.17; 95% confidence interval, 1.01–1.36). GRS153 had no association with either recurrent ACS or composite of recurrent ACS or death. Also, GRS47 was associated inversely with smoking and ST-segment–elevation myocardial infarction ( P =0.004; odds ratio, 0.22; 95% confidence interval, 0.08–0.62 and P =0.041; odds ratio, 0.36; 95% confidence interval, 0.13–0.96, respectively). Conclusions—: GRSs combined of 47 known coronary artery disease risk single-nucleotide polymorphisms were associated with recurrent ACS after multivariable adjustments in a heterogenic ACS population for the first time. Smoking and ST-segment–elevation myocardial infarction had an inverse association with the GRSs. The significance of smoking in relation to genetic coronary artery disease predisposition may merit further evaluation in patients with ACS. Abstract : Supplemental Digital Content is available in the text.